A note on large-scale land acquisitions, commitment problems and international law - Yorck Diergarten; Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2015)
Poorly developed countries with weak institutions often face severe commitment problems. International investors are reluctant to invest in these countries because their property rights are insufficiently protected. We argue that in order to overcome the commitment problem countries may subject investors' rights protection to independent investment tribunals. These tribunals are known to strictly support property rights protection and to be reluctant to honor human rights considerations, although they might be applicable. This may explain why human rights of the local smallholders in large-scale land acquisitions are hardly protected in the Global South.
Keywords: 330; large-scale land acquisitions; land grabbing; law & economics; international law; property rights; commitment problems; foreign investors; weak institutions